Perangkat Penyimpanan Muatan Listrik Ramah Lingkungan Berbasis Karbon Aktif Dari Limbah Hasil Pengolahan Muntok White Pipper - Ipi, Ipi; Safitri, Aisyah Deri Ayu Tungga; Febriani, Yunita; Kurniawan, Widodo Budi; Megiyo, Megiyo (Jurusan Fisika, Universitas Bangka Belitung, 2021)
The national need for advanced materials is spread across several fields, such as industry, transportation, information systems and military defense systems. In the field of transportation, the government continues to innovate by shifting fuel-based vehicles (BBM) towards environmentally friendly cars in the form of electric cars. However, the main challenges in developing this electric car are the electric energy charge storage system which is durable, has high storage capacity, and short charging time. In this study, carbon was activated gradually using a 7% H3PO4 solution followed by heating at a temperature of 700oC for 3 hours under nitrogen gas (N2). The results of the FTIR analysis showed that the activated carbon N2 gas had a strong and sharp C=C group along the absorption band 1500 cm-1 – 1400 cm-1 which indicated that the activated carbon had high quality and purity. This result was strengthened based on the EDS spectra which showed a carbon content of 90.56%. In addition, based on SEM micrographs, it can be observed that the morphology of the carbon produced has pores scattered on the surface. The presence of these pores will provide space for the transfer of charge or ions to the electrode. The best electrode was obtained on activated carbon with N2 gas activation treatment with a conductivity of 3.92 x 10-2 S/m and a capacitance of 1.44 x 10-3 F, so it was concluded that activated carbon muntok white paper can be used as an electric charge storage material.